2019
DOI: 10.1101/684431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A geographical cline in craniofacial morphology across populations of Mesoamerican lake-dwelling fishes

Abstract: The complex geological history and tropical climate of Mesoamerica create a rich source of biodiversity from which we can study evolutionary processes. Here, we discuss highly divergent forms of lake-dwelling fishes distributed across southern Mexico and Central America, originally recognized as members of different genera (Astyanax and Bramocharax). Recent phylogenetic studies suggest these morphotypes group within the same genus and readily hybridize. Despite genetic similarities, Bramocharax morphs exhibit … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Genetic evidence suggests that at least in one cave (Chica), an admixture occurs between individuals of A. mexicanus from surface and cave waters (Bradic et al, 2012;Strecker, Hausdorf & Wilkens, 2012;Herman et al, 2018). Another conspicuous example of parallel evolution under ecologically divergent scenarios within the genus is shown by the sympatric lacustrine species across Mexican and Central America tropical lakes, that is A. aeneus and A. caballeroi; A. nasatus, A. nicaraguensis and A. bransfordii (Ornelas-García et al, 2008;Powers et al, 2020). In Lake Catemaco, Mexico, the morphs of A. aeneus and A. caballeroi are highly divergent, and as a result, they were originally considered as different genera (Astyanax and 'Bramocharax'); however, recent molecular studies have shown that they belong not only to the same genus, but also they readily hybridize and show no sign of genetic differentiation, although morphological and ecological differences are evident among Astyanax ecomorphs (Ornelas-García et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic evidence suggests that at least in one cave (Chica), an admixture occurs between individuals of A. mexicanus from surface and cave waters (Bradic et al, 2012;Strecker, Hausdorf & Wilkens, 2012;Herman et al, 2018). Another conspicuous example of parallel evolution under ecologically divergent scenarios within the genus is shown by the sympatric lacustrine species across Mexican and Central America tropical lakes, that is A. aeneus and A. caballeroi; A. nasatus, A. nicaraguensis and A. bransfordii (Ornelas-García et al, 2008;Powers et al, 2020). In Lake Catemaco, Mexico, the morphs of A. aeneus and A. caballeroi are highly divergent, and as a result, they were originally considered as different genera (Astyanax and 'Bramocharax'); however, recent molecular studies have shown that they belong not only to the same genus, but also they readily hybridize and show no sign of genetic differentiation, although morphological and ecological differences are evident among Astyanax ecomorphs (Ornelas-García et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Astyanax found in Lake Catemaco may correspond to a less divergent lineage of the genus than that in the San Juan River basin (Ornelas‐García et al, 2008), which could represent a more divergent lineage with discrete levels of genetic differentiation. Congruent with this genetic divergence, Garita‐Alvarado et al (2018) and Powers et al (2020) found more morphological divergence between morphs in the San Juan River system than in Lake Catemaco. Additionally, besides time, Nosil et al (2009) noted other factors that could influence the ecological speciation process, like the nature of the divergent selection, being strong or weak, acting on a single trait or on a larger number of traits, or genetic factors such as no physical linkage between genes under selection and those conferring reproductive isolation.…”
Section: Discussionmentioning
confidence: 95%
“…An excellent system in which to assess mechanisms promoting and maintaining diversity is the freshwater fish genus Astyanax (Baird & Girard, 1854), given its remarkable adaptability to diverse environmental conditions (Jeffery, 2009) and its presence in lake and river environments. Previous studies have shown the high lacustrine diversification capacity of Astyanax (Garita‐Alvarado et al, 2018; Powers et al, 2020), particularly in the San Juan River basin, which includes two large Nicaraguan lakes, Managua and Nicaragua, and their associated outflow river, the San Juan. In this basin, two very distinct morphs (elongate‐body and deep‐body) of Astyanax coexist in sympatry (Garita‐Alvarado et al, 2018), raising questions about the degree of morphological divergence, ecological specialization and reproductive isolation shown by the morphs, and the links between these factors.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations